Manejo de plantas daninhas e sua relação com a produtividade e potencial fisiológico de sementes de feijoeiro - da Costa, Denis Santiago; Barbosa, Rafael Marani [UNESP]; de Sá, Marco Eustáquio [UNESP] (FapUNIFESP (SciELO), 2013)
Common bean is an important crop in Brazil primarily because of its nutritional characteristics. Some agronomic practices, such as weed management, are fundamental to cultivation, as a means of obtaining a high crop yield. However, some studies have shown that weed management may alter the function of the cultivar cycle. Thus, this study aimed at determining the optimal phenological stage in early-maturing common bean cultivars to perform the weed control without providing reductions in yield and seed quality. The experimental design was randomized blocks with 20 treatments and four replications, in a 2×2×5 (cultivars × types of weed control × periods of weed control) factorial scheme. The periods of weed control for both cultivars (Carioca Precoce and IPR-Colibri) consisted of full cycle weeded (control), weed control at the V4-3 stage (first three nodes on the main stem with trifoliate leaves), at the R5 stage (beginning of bloom) and at the R8 stage (appearance of pods) and full cycle unweeded (no weed control). The types of weed control used were chemical (fluazifop-p-butyl + fomesafen) and mechanical (hoe). The Carioca Precoce cultivar demonstrated higher agronomic performance and yield than the IPR-Colibri cultivar, although the IPR-Colibri seeds had a higher vigor. The type of weed control (chemical or mechanical) did not affect the agronomic characteristics, yield and seed physiological potential of the cultivars. The ideal period for weed control in early-maturing common bean cultivars to obtain a higher yield and seed physiological potential was observed at the V4-3 phenological stage.
Weed management and its relation to yield and seed physiological potential in common bean cultivars
Keywords: Phaseolus vulgaris L.; Seed vigor; Weed competition